Transformation Of Islamic Education Management In The Digital Era: Trends And Implications For Learning Quality - Holilah Holilah; Wafi Ali Hajjaj (Journal of International Multidisciplinary Research, 2024)
This research aims to examine the transformation of Islamic education management in the digital era and its implications for the quality of learning, with a focus on the innovation of technology use in teaching and administration. This research uses a descriptive qualitative approach, collecting data through interviews, observations, and documentation in several Islamic educational institutions that have implemented digital technology. Research results reveal that the adoption of technology such as Learning Management Systems (LMS), e-learning platforms, and administrative digitization has improved the effectiveness of the learning process and the efficiency of school management. The findings also indicate that this transformation brings significant changes to the organizational culture, creating higher transparency and accountability in the management of educational institutions. The novelty of this research lies in the comprehensive analysis of the challenges and strategies faced by Islamic educational institutions in aligning technological advancements with traditional values, as well as the emphasis on the importance of continuous training for educators to enhance technological competence. Nevertheless, there are still obstacles such as limited infrastructure and a lack of digital literacy among educators. This research concludes that digital transformation in Islamic educational institutions offers great potential in improving the quality of education, provided it is accompanied by the enhancement of educators' capacities and equitable access to technology